The diatom genus Tetracyclus (Fragilariaceae, Bacillariophyta) from Chile - Williams, David M. (Phytotaxa, 2014)
Ehrenberg referred only once to the diatom species Biblarium chilense Ehrenb. (1854: 301, 303, nom. nud.) in the text to his Mikrogeologie (Ehrenberg, 1854). His comments are relatively uninformative; he never published an illustration: “B[iblarium] chilense ist eine dem Bibl. compressum verwandte neue Art” (Ehrenberg, 1854: 301, and noted in the table on p. 303) “B[iblarium] chilense is a new species related to Bibl. compressum” (translation modified after Ralfs in Pritchard, 1862: 806) Consequently the name Biblarium chilense is a nomen nudum. Even so, some years later De Toni, observing neither illustration nor specimen, transferred it to Tetracyclus as Tetracyclus (chilensis) chilense (Ehrenb.) De Toni (De Toni 1892: 749).